The Effect of PJBL and IBL on the Learning Independence of Vocational School Students - Prihatin, Relly; Sukmawati , Fatma; Cahyono, Budi Tri; Santosa, Eka Budho; Juwita, Ratna; Suparmi (Pascasarjana Universitas KH. Abdul Chalim, 2024)
The influence of Project Based Learning (PJBL) and Inquiry-Based Learning (IBL) learning models on students' learning independence at SMK Solo. PJBL and IBL were chosen as innovative and student-centred learning models, focusing on increasing students' independence and active involvement in the learning process. Based on the results of data analysis, it was found that PJBL provided a significant increase in student independence, with an average pre-test score of 44.01, increasing to 70.38 in the post-test. Meanwhile, students who took IBL experienced an increase from 46.85 to 59.77. The t-test showed a significant difference between the pre-test and post-test with a significance value of 0.000 (sig <0.05), indicating that both learning models contributed positively to increasing student independence. The results of the multivariate analysis supported this finding, with an F value of 3.052 and a significance of 0.018 (sig <0.05), indicating that PJBL was more effective than IBL in increasing independence. However, in the aspect of student creativity, no significant difference was found between the two models, with a significance value of 0.157 (sig > 0.05). In conclusion, PJBL is superior in encouraging student independence compared to IBL, and the results of this study provide important recommendations for educators to prioritize PJBL in the context of learning that focuses on developing student independence in vocational schools.